REPRESENTASI KETIDAKSETARAAN GENDER DALAM PROGRAM TELEVISI - restiawan permana (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2016)
As a product of the media, talk shows can be culture 'text' that interacts with viewers in the production and exchange of meaning. Almost all programs talk shows on television to attract people to watch it. Indulgence of society in the program caused by several factors, such as the show that is entertaining, any informative, educative, and inspiring messages contained in the talk show. Moreover, were guided by a reliable host emceeing, or by bringing in a competent and influential resource for the community. In this study, the authors chose two talk shows to being the object of research. Both of these talk shows that